Cutting-edge technologies and social media use in higher education - Benson, Vladlena, 1976-; Morgan, Stephanie J.; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2014)
"This book brings together research on the multi-faceted nature and overarching impact of social technologies on the main opportunities and challenges facing today's post-secondary classrooms, from issues of social capital formation to student support and recruitment"--Provided by publisher.
Facing Facebook in higher education: how and why students use Facebook in college / Karen Abney Korn -- Students' privacy concerns on the use of social media in higher education / Laura Aymerich-Franch, Maddalena Fedele -- Overcoming organizational obstacles and driving change: the implementation of social media / Jenni Murphy, Anna Keck -- The use of social media in the networking strategy of higher education institutions: the Polish experience / Tomasz Domanski, Michal Sedkowski -- Reaching them where they live: effectively utilizing the social media literacy of c-borgs in higher education and beyond / Danielle Lawson -- #OccupyWallStreet: social media, education, and the Occupy movement / Adam Gismondi -- The roadmap for experimental teaching of science and engineering based subjects: innovative technology and social media in higher education / Gordana Collier, Andy Augousti, Andrzej Ordys -- Leveraging Facebook as a peer-support group for students / Joni Salminen -- Social media as technologies for asynchronous formal writing and synchronous paragraph writing in the South African higher education context / Chaka Chaka -- Recognised creativity: the influence of process, social needs, and the third drive on creative individuals' work through social media / Monika Musial, Antti Kauppinen, Vesa Puhakka -- The use of social media in college recruiting and the student job search / Amy Diepenbrock, Wanda Gibson -- Leveraging new media as social capital for diversity officers: a how-to guide for equity, diversity, and inclusion professionals seeking to use social media to carve a niche in the social networking space / Kindra Cotton, Denise O'Neil Green -- Teaching students about online professionalism: enhancing student employability through social media / Thomas Lancaster -- The utilization of online boundaries: Facebook, higher education, and social capital / Lewis A. Luartz -- Social media for knowledge workers / Ikbal Maulana -- Justifying the ROI of social media investment in education / Vladlena Benson, Stephanie Morgan.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 02/28/2014).
Keywords: Education, Higher -- Effect of technological innovations on; Education, Higher -- Social aspects; Educational technology -- Social aspects; Social media; Social media in higher education; Business applications; Emerging technologies; Employability; Knowledge management; Online networks; Privacy; Reputation management; Social capital; Social marketing; Student engagement; Electronic books